A corpus-based assessment of vocabulary in interpreting textbooks - Dandan Sheng; Xin Li (Humanities & Social Sciences Communications)
Abstract Undergraduate interpreting training programs rely heavily on high-quality textbooks to develop student interpreters’ interpreting competence. However, there is limited empirical research assessing the vocabulary of interpreting textbooks, leaving a gap in understanding their lexical demands and pedagogical effectiveness. This study addresses this gap by evaluating the English vocabulary of undergraduate interpreting textbooks from the perspectives of vocabulary load, frequency distribution, and repetition patterns. Based on a corpus of two textbooks on interpreting between Chinese and English widely used in undergraduate interpreting training programs in the Chinese Mainland, the study finds that both textbooks require student interpreter users to possess a productive vocabulary of 3000 to 5000 word families (plus words from supplementary lists). Also, both textbooks feature the highest proportion of high-frequency words, provide an opportunity to learn mid-frequency words dominated by the third 1000 word families, and present low-frequency words concerning trending topics associated with social life in both international and domestic contexts during a certain period. Moreover, they lack words repeating at least five times across book units, while words appearing in only one unit account for a high proportion. This vocabulary assessment also provides an approach to differentiate between textbooks in the abovementioned aspects. With no vocabulary list predefined in the syllabus, this corpus-based approach of textbook vocabulary assessment can empower textbook evaluation by providing quantitative evidence for textbook suitability and usability, thereby aiding interpreting textbook writers and teachers in promoting students’ language competence, subject matter knowledge, interpreting ability, and the cultivation of values.